1H, 13C NMR studies of new 3‐aminophenol isomers linked to pyridinium salts. (30th October 2013) - Schiaffino‐Ortega, Santiago; Espinosa, Antonio; Gallo, Miguel A.; López‐Cara, L. Carlota; Entrena, Antonio
<x xml:space="preserve">Abstract</x> 1H and 13C NMR spectroscopic data of 20 new non‐symmetrical compounds were assigned by a combination of 1D and 2D NMR experiments (DEPT, HSQC, and HMBC). These compounds contain a 4‐(N, N‐dimethylamino)‐ or 4‐(pyrrolidin‐1‐yl)pyridinium moiety and a 3‐nitro‐, 3‐amino‐, or 3‐hydroxyphenyl ring, linked by p‐xylene, 4, 4′‐dimethylbiphenyl, 1, 2‐bis(p‐tolyl)ethane, or 1, 4‐bis(p‐tolyl)butane. Copyright © 2013 John Wiley & Sons, Ltd.